Parametric methods for beginners : architecture applications - Toker, Umut (New York : Routledge/Taylor & Francis Group, 2023)
"This book introduces architectural applications of parametric methods in design, drawing direct connections between each phase of the architectural design process with relevant parametric approaches. Readers will find applications of parametric methods with straightforward explanations of concepts, commands as well as applicable examples for each phase of the architectural design process. In addition to learning about the historical and conceptual background of parametric design, readers can use this book as a go-to source during their day-to-day design practice. Chapters are organized according to different phases of the architectural design process, such as site analysis, spatial organization, skin systems, and environmental performance analyses. Together, they deliver concepts, applications and examples utilizing in-depth visual guides that explain commands, their outcomes and their interrelationships. With over 350 images, this book includes examples from the author's own design studio and parametric design teaching in elective classes. Based on the Rhinocerous and Grasshopper platforms, this book is an accessible, yet in-depth resource for architecture students and early professionals who are considering integrating parametric applications into their design processes"--
Includes bibliographical references.
Keywords: Rhino (Computer file); Architectural design -- Data processing; Architecture -- Mathematics; Parameter estimation